STUDI ANALISIS HIASAN SULAMAN BENANG PADA KAIN KATUN VALENTINO UNTUK BUSANA CASUAL WANITA (Universitas PGRI Adi Buana Surabaya, 2024)
The background of the study are the fact of casual clothing display in many of variation of clothing ornament. The material used for making the casual clothing is valentino cotton which given threads embroidery ornament.The statement of the problem is